2017
DOI: 10.3389/fams.2017.00019
|View full text |Cite
|
Sign up to set email alerts
|

Specifying Turning Point in Piecewise Growth Curve Models: Challenges and Solutions

Abstract: Piecewise growth curve model (PGCM) is often used when the underlying growth process is not linear and is hypothesized to consist of phasic developments connected by turning points (or knots or change points). When fitting a PGCM, the conventional practice is to specify turning points a priori. However, the true turning points are often unknown and misspecifications of turning points may occur. The study examined the consequences of turning point misspecifications on growth parameter estimates and evaluated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…To answer the research questions, piecewise growth curve models (PGCM) were computed in Mplus version 8.0. In piecewise growth curve models, researchers identify a turning point or knot in a curvilinear growth trend and use this to separate the trend into separate slopes, to compare them (Ning & Luo, 2017). This presents an ideal model to test growth across the mid-schooling transition (W1 -W3) versus across the school-to-work transition (W3 -W5).…”
Section: Data Modellingmentioning
confidence: 99%
“…To answer the research questions, piecewise growth curve models (PGCM) were computed in Mplus version 8.0. In piecewise growth curve models, researchers identify a turning point or knot in a curvilinear growth trend and use this to separate the trend into separate slopes, to compare them (Ning & Luo, 2017). This presents an ideal model to test growth across the mid-schooling transition (W1 -W3) versus across the school-to-work transition (W3 -W5).…”
Section: Data Modellingmentioning
confidence: 99%
“…In some cases, analysts might not know the turning points and need to discover them inductively. A recent paper by Ning and Luo (2017) gives some directions on how this might be done. 9 A second issue is that national-level contextual effects are often endogenous, and simultaneity is often the cause.…”
Section: Lessons About Two-piece Growth Curve Modelsmentioning
confidence: 99%
“…Although the sample size of the Spring 2019 cohort was roughly half that of the Fall 2018 cohort, the large fraction of residual variance indicated that misfit derived from misspecification—the linear and quadratic shape parameters did not describe the data well. Although it is possible to specify more complex shape parameters in LGCM, this approach extended beyond our objectives and was not suggested by our data (Ning & Luo, 2017). As a result, we concluded that Spring 2019 individual interest showed no consistent shape patterns, and its trajectory was obscured substantially by both within‐ and between‐individual variation.…”
Section: Resultsmentioning
confidence: 99%